The Ecclesiology of Pope Francis: A Critical Analysis of the Metaphor of the Church as Polyhedron - Željko Tanjić; Zoran Turza (Bogoslovni Vestnik, 2023)
Pope Francis focuses on essential topics for the Church and society in his pontificate. To describe the relationships between different social subjects, he often uses the metaphor of the polyhedron to highlight the importance of each individual and each social group for the equitable development of the entire society. Nowhere does it systematically describe this metaphor, but it uses it in different contexts: societal, ecclesial, ecumenical, and theological. The literature also lacks papers that systematically and critically question this metaphor, presenting possible consequences for the Church’s life, i.e., pastoral care, liturgical practices, morality, doctrine, etc. This paper aims to describe this metaphor of the Church as a polyhedron. The metaphor of the polyhedron that he uses in his documents will be described first. Then, the key features, advantages, and disadvantages of the metaphor of the Church as a polyhedron will be brought out. According to this metaphor, the Church can be understood through her main characteristics: as synodal Church, unity in diversity, missionary Church, and charity.